(untitled) (REGE Revista de Gestão, 2018)
AbstractPurpose – Studying the gap between improvements in operational performance of a manufacturingorganization does not necessarily represent the existent of safe and healthy work. The purpose of this paper isto fill this gap validating a scale about social practices. Design/methodology/approach – The literature was studied; data analysis instrument and the scalevalidated by Q-sort. The reliability and validity of research instrument indicators were drawing from theanalysis of judges. The data were assessed by convergence matrix. Findings – It was validated five social practices factors. It was enabled the adequacy of the name of theconstructs and establishment which indicators better convergence to the constructs.Research limitations/implications – The judge´s number that answered the research was low. The levelof convergence related of two factors was above 50 percent. Practical implications – It is possible to achieve better levels of performance through social practices.Organizationsmust rethink the management and the routine of the workers to implement the operational practices. Social implications – The practices need to have with well-defined rules, as well as action to drivecompliance. This vision also needs to be expanded to suppliers, customers and society. Originality/value – Highlight five points: technology is the main factor for analyzes and decisions; thesearch for quality leads organizations to seek practices that improve workers’ well-being, health and safety;the activities of the worker are carried out on the factory, or in the work environment; Should not to belittle thelocal community; culture is an essential factor to continuous improvement. Keywords Sustainability, Scale development, Social practice, Health and safety at work, Q-sort